New antirheumatic substance based on phenolic glycoside structure methyl (4-О-Β-glucopyranosyloxy)-benzoic acid; Jurnal Teknologi; Vol. 78, iss. 6-8 - Nemtsev A. O. Aleksey Olegovich; Smirnov I. V. Ivan Vladimirovich; Murashko T. O. Tatjyana Olegovna; Ivanov A. A. Aleksey Alekseevich; Bondarev A. A. Aleksandr Aleksandrovich; Udut V. V. Vladimir Vasiljevich (2016, 2016)
Title screen